Communication Dynamics and Their Impact on Librarian Service Performance in Academic Institutions - Dinata, Yuriyan; Setyaningsih, Rini (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study examines the relationship between communication practices and librarian performance at the Library of the State Islamic University of Sultan Syarif Kasim Riau, Indonesia. Communication is a central factor in determining organizational success, particularly in service-oriented institutions such as libraries, where interpersonal interaction and customer satisfaction are critical performance indicators. Using a qualitative case study approach, the research explores how librarians communicate with colleagues, superiors, and visitors, and how these interactions influence job performance. Data were collected through observation, interviews, and documentation, involving senior librarians, staff members, and library users. The findings reveal that effective and courteous communication fosters a collaborative, comfortable, and productive work atmosphere, which directly contributes to improved performance outcomes. Informal yet respectful internal communication among staff and leadership was found to enhance teamwork and reduce hierarchical tension, while polite and responsive communication with library users significantly increased visitor satisfaction and service reputation. The study concludes that positive communication behaviors not only improve service quality but also serve as a catalyst for performance improvement and organizational harmony within higher education libraries.